2006
DOI: 10.1007/s11055-006-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of apoptosis in different parts of the brain during learning

Abstract: Caspase-3 activity and the levels of DNA fragments of 200-600 and >4000 b.p. were estimated in the cerebellar vermis, the hippocampus, and the prefrontal cortex of the brains of adult rats four and 24 months after training to extinction of the acoustic startle reaction and conditioned fear. Differently timed changes in the levels of biochemical markers of apoptosis were seen to different extents in these brain areas after training. These changes were characterized by a decrease in caspase-3 activity in the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…For example, protein сaspase-3 which is regarded as a key link in caspase dependent apoptosis [33] is known to be involved in molecular mechanisms of learning and memory [34,35] based on the principles of brain regional specificity and heterochrony [36]. Addressing this concern, a recent study reported that caspase-3 participates not only in processes of programmed cell death but also neuronal plasticity [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, protein сaspase-3 which is regarded as a key link in caspase dependent apoptosis [33] is known to be involved in molecular mechanisms of learning and memory [34,35] based on the principles of brain regional specificity and heterochrony [36]. Addressing this concern, a recent study reported that caspase-3 participates not only in processes of programmed cell death but also neuronal plasticity [37].…”
Section: Discussionmentioning
confidence: 99%
“…As caspase 3 has been linked to physiological plasticity downstream of NMDA receptor stimulation in the CNS (Sherstnev et al. , 2006; Li et al.…”
Section: Resultsmentioning
confidence: 99%
“…Basal caspase 3 activity was detected in both cortex and cerebellum from the brains of adult WT mice. This caspase 3 activity may conceivably relate to physiological processes, including synaptic plasticity and learning (Sherstnev et al. , 2006; Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations